1997
DOI: 10.1080/095530097143608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy ions on the germination and survival of Arabidopsis thaliana

Abstract: Inhibition of germination and reduction in survival of Arabidopsis thaliana were investigated to study the effects of heavy ions on a multicellular system. Dry seeds of Col and Ler ecotypes were exposed to He, C, Ar and Ne ions with linear energy transfer (LET) in the range of 17-549 keV/micron and to electrons (LET = 0.2 keV/micron). The relative biological effectiveness (RBE) for the survival of both ecotypes showed the same pattern of variation with a maximum RBE of 11-12 at 252 keV/micron. For germination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Ion beams have high linear energy transfer (LET) and higher biological eVects than radiations with low LET such as gamma rays (Fujii et al 1966;Hirono et al 1970;Mei et al 1994;Tanaka et al 1997). Owing to these diVerences, ion beams are expected to have higher mutation induction eVects than gamma rays.…”
Section: Introductionmentioning
confidence: 97%
“…Ion beams have high linear energy transfer (LET) and higher biological eVects than radiations with low LET such as gamma rays (Fujii et al 1966;Hirono et al 1970;Mei et al 1994;Tanaka et al 1997). Owing to these diVerences, ion beams are expected to have higher mutation induction eVects than gamma rays.…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have reported that high-LET radiations confer greater and more distinctive biological effects on plant cells than low-LET radiations. For instance, high-LET radiations produce a more lethal effect on Arabidopsis and tobacco cells [ 6 9 ]. As for the types of mutation, irradiation of Arabidopsis dry seeds by carbon ion beams induces point-like mutations (base substitutions and several-base deletions/insertions) and chromosomal rearrangements with similar frequencies, whereas electron beams, one of the low-LET forms of radiation, predominantly induce point-like mutations [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 150 seeds were placed in a Petri dish with their embryos facing upward. Irradiation apparatus for dry seeds, which was connected to a vertical beam line of an azimuthally varying field (AVF) cyclotron (Japan Atomic Energy Agency, Takasaki, Japan) [27], was used for carbon-ion irradiation with the total energy of 320 MeV (26.7 MeV/u). The linear energy transfer was calculated as 76 keV/μm at the sample surface.…”
Section: Methodsmentioning
confidence: 99%